Antioxidant and Anti-inflammatory Properties of Peptide Fractions of Morinda lucida and Alstonia boonei and Protective Effects against Lead-induced Toxicity in Drosophila melanogaster - Zainab Abiodun Molik; Amos Olalekan Abolaji; Omonike Oluyemisi Ogbole (Biology, Medicine, & Natural Product Chemistry, 2025)
Morinda lucida and Alstonia boonei are widely used in ethnomedicine for treating and managing various ailments and have been validated for several biological activities. This study investigated the antioxidant and anti-inflammatory properties of partially purified peptide fractions of Morinda lucida (MLP) and Alstonia boonei (ABP) and their protective effect against lead (Pb)-induced toxicity on wild-type Drosophila melanogaster. Peptide fractions were partially purified using solid phase extraction and evaluated for antioxidant activities using 2,2-diphenyl-1-picrylhyhdrazyl (DPPH) radical scavenging activity and ferric reducing antioxidant power (FRAP) assays. Anti-inflammatory activity was assessed via protein denaturation and membrane stabilisation assays. Flies were treated with Pb (10 mM), peptide fractions (50 and 100 µg/10g diet), and co-treatment of Pb plus the fractions. After treatment, homogenized flies were analysed for total thiol (TSH) and non-protein thiol (NPSH) content, glutathione-S-transferase (GST) activity, nitric oxide (NO) (nitrite/nitrate) and hydroperoxide levels. The peptide fractions showed significant in vitro antioxidant and anti-inflammatory properties. Both fractions (50 and 100 µg/10g diet) maintained a balanced redox status of flies. Pb exposure reduced survival rates and increased oxidative stress markers compared to control untreated flies. Co-treatment with MLP and ABP (50 and 100 µg/10g diet) improved antioxidant enzyme activities (GST, NPSH and Total thiol) and accumulation of NO and hydroperoxide in Pb-treated flies. Therefore, the peptide fractions from M. lucida and A. boonei may be sources of bioactive agents with therapeutic potential against oxidative stress and inflammation associated with lead toxicity.